Higher education, emerging technologies, and community partnerships : concepts, models and practices - Carpenter, Russell G., 1979-; Bowdon, Melody A., 1967- (Information Science Reference, 2011)
"This book is a comprehensive collection of research with an emphasis on emerging technologies, community value, and corporate partnerships, providing strategies to implement partnerships"--Provided by publisher.